Adapting the Shield: Ensuring Military Readiness for Flood Disaster in Malaysia’s - Yatim, Lilis Asyura M.; Abdul Munir, Zarina; Razak, Norfadzilah A.; Bahry, Norliza S.; Mat, Azmi; Kori, Nur Liana (Advances in Social Sciences Research Journal, 2024)
The number of disasters is increasing day by day all over the world. In Malaysia, several peninsular states are frequently overwhelmed by flooding during the monsoon season. The military has played an imperative role in disaster management and relief. The Malaysian Armed Forces are well-trained in terms of combat. However, disaster relief is a secondary part of their social responsibilities. Malaysian Armed Forces members still try their best to complete the assigned task with total commitment, even though they have not had any specific training on this matter. There are lots of studies found that relate to the knowledge and attitude of nurses and health providers towards flood disaster management; however, more research needs to be conducted among Malaysian Armed Forces members. Due to this matter, this paper was developed to scrutinize Malaysian Armed Forces members’ knowledge, willingness, and attitude toward flood disaster preparedness. This research will be based on a quantitative method distributed to the Malaysian Armed Forces members in the Ministry of Defense. Questionnaires were distributed online to the respondents among Malaysian Armed Forces members in the Ministry of Defense. The study managed to get 264 respondents from Malaysian Armed Forces members in three different services: the Army, Navy, and Air Force. The data is analyzed using descriptive, reliable, and regression analysis using the Statistical Package for Social Science (SPSS). Apart from that, regression analysis was used to test the hypothesis in this study. The finding found that knowledge of flood disaster preparedness and willingness/attitude is significant towards flood disaster preparedness. The findings imply effective practices and strategies applied by the Malaysian Armed Forces in facing disasters in the future.